Towards more intentional language policy in higher education: A case study of a Greek University - Motsiou, Eleni; Kostoulas, Achilleas (Neofilolog, 2025)
Universities are institutions for the production and transmission of knowledge; they are also fields of power negotiation between social groups, which is expressed through linguistic policies. The presence or absence of Less Widely Used Languages in this context is interpreted in relation to the social power of dominant languages. This article presents a case study of the linguistic policy of a university in Greece aiming to highlight the role of dominant languages (Standard Modern Greek and International English) in a linguistically complex ecosystem. The marginalization of local languages through hegemonic processes of regulation and imposition of Standard Modern Greek is noted. Ιt is also pointed out that the teaching of certain ‘high prestige’ foreign languages, which are not considered a threat to the hegemonic status of Greek, is allowed. Since this correlation is reinforced by the lack of a defined policy for linguistic inclusion and the enhancement of linguistic diversity, a series of actions aimed at creating a targeted linguistic policy is proposed.